2003
DOI: 10.1073/pnas.1531957100
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen receptor-α mediates the brain antiinflammatory activity of estradiol

Abstract: Beyond the key role in reproductive and cognitive functions, estrogens have been shown to protect against neurodegeneration associated with acute and chronic injuries of the adult brain. Current hypotheses reconcile this activity with a direct effect of 17␤-estradiol (E 2 ) on neurons. Here we demonstrate that brain macrophages are also involved in E2 action on the brain. Systemic administration of hormone prevents, in a time-and dose-dependent manner, the activation of microglia and the recruitment of periphe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
294
4
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 353 publications
(332 citation statements)
references
References 47 publications
(47 reference statements)
28
294
4
6
Order By: Relevance
“…With regard to microglia, in the recent years our studies showed a major anti-inflammatory activity of estradiol in microglia activated by strong inflammatory stimuli such as lipopolysaccharide (LPS) [241]. This effect was antagonized by ICI182,780, an estrogen receptor antagonist, suggesting a receptor-mediated effect of the hormone and ERa appeared to be selectively involved in estradiol anti-inflammatory activity in brain macrophages ( [82,242]). Other authors further confirmed these observations using primary cultures of microglia as well as cell lines and assaying estrogen-dependent attenuation of microglia activation in terms of reduced phagocytic activity, production of reactive oxygen and nitrogen species and other factors of the inflammatory cascade ( [26,43,61,141,262]).…”
Section: Estrogens and Microgliamentioning
confidence: 92%
See 4 more Smart Citations
“…With regard to microglia, in the recent years our studies showed a major anti-inflammatory activity of estradiol in microglia activated by strong inflammatory stimuli such as lipopolysaccharide (LPS) [241]. This effect was antagonized by ICI182,780, an estrogen receptor antagonist, suggesting a receptor-mediated effect of the hormone and ERa appeared to be selectively involved in estradiol anti-inflammatory activity in brain macrophages ( [82,242]). Other authors further confirmed these observations using primary cultures of microglia as well as cell lines and assaying estrogen-dependent attenuation of microglia activation in terms of reduced phagocytic activity, production of reactive oxygen and nitrogen species and other factors of the inflammatory cascade ( [26,43,61,141,262]).…”
Section: Estrogens and Microgliamentioning
confidence: 92%
“…In fact, estradiol does not alter the inflammatory signaling cascade in microglia if it is administered after inflammatory stimuli ( [26,82,242]); in addition, a prolonged hormonal deprivation affects estrogen protective activity in ischemia and causes a null or even opposite response to exogenous hormone administration [224]. Collectively, the experimental Fig.…”
Section: The Timing Hypothesismentioning
confidence: 94%
See 3 more Smart Citations